AKSINA Education with Crossword Puzzle on Knowledge of Earthquake Disaster Preparedness in Elementary School Students - Km Indah Kusuma Dewi, Ni; G. A. Ari Rasdini, I.; Pt. Gd. Putra Yasa, I Dw.; Made Wedri, Ni (KHD-Production, 2024)
Based on data from the Badan Nasional Penanggulangan Bencana (BNPB) in 2016, out of the 2000 biggest disasters including earthquakes that occurred in Indonesia, the most victims were children. Disaster preparedness education can be carried out early on in schools so that children know how to avoid and save themselves from disasters. This study aims to determine the effect of education